EFEK FISHER DI INDONESIA: PENDEKATAN CO-INTEGRATION DAN ERROR CORRECTION MODEL (ECM) - Sri Fatmawati; Algifari Algifari (Fakultas Bisnis UKDW, 2015)
The aim of this research is to examine the existence of Fisher Effect for Indonesian Economy, by regressing interest rate on rate of inflation in period 1980-2011. With co-integration and error correction technique, the results indicate that an increases of one percent in inflation rate lead to increase in interest rate at 0,13 percent in short-run and at 0,95 percent in longrun. This research can’t confirm the existence of Fisher Effect in Indonesian Economy in short-run, but this effect exists in long-run. Keywords: Fisher Effect, Interest Rate, Inflation Rate, Co-integration, Error Correction Model